USE OF NURSING DELEGATION IN IMPROVING PATIENT CARE EFFICIENCY - Asma Aied Safah Aldafeeri, Bashair Ghanim Aldafeeri, Zahi Foriaan Alanazi, Eshraq Awad Al Johany, Amna Nasser Suliman, Abdullah Ali Algahtane, Bedoor Mudasher Alenazi, Hana Oudah Alshammrei, Raghad Alshammari, ,; Abdullah Hamoud Ali Alqahtani, Bader Fahad Munahi Alotaibi, Majed Eid Aljohani, Mohammed Abdullah Mohammed Alharthi, ,; Fatemah Abdullah Hussain Alidrisi, Hind Marzouq Alsaud, (Chelonian Research Foundation, 2022)
The healthcare industry is now encountering several difficulties, such as the aging of populations, the rising occurrence of chronic illnesses, and a shortage of registered nurses. The practice of using unregistered support workers is widespread in several nations as a means to enhance the service capacity of nursing teams. Non-registered support workers are assigned the responsibility of administering medicine, which is seen as a complicated undertaking that has inherent hazards. Given the projected worldwide rise of patients need assistance with medicine in community settings, this is a significant subject. This study examines the data about the transfer of medicine administration responsibilities from registered nurses to non-registered support workers in community settings. The goal is to get a better understanding of the elements that affect the delegation process and its effects on service provision and patient care. The review adhered to the fundamental concepts of Critical Interpretative Synthesis and was organized according to the recommendations outlined in Preferred Reporting Items for Systematic Reviews and Meta-analysis. Systematic searches were performed in the MEDLINE, CINAHL, Embase, and ProQuest-British Nursing Index databases. The introduction of delegating drug administration was affected by regulatory issues, communication, stakeholder participation, and service advocates. The process of delegating drug administration is complex and impacted by several interconnected elements. Clear and consistent regulatory and governance structures and processes are necessary in order to mitigate the heightened risk associated with pharmaceutical delivery. Medication administration delegation is more acceptable when it is supported by a framework that includes suitable policies, skills, training, and supervising procedures. Additional study is necessary to investigate the implementation process, clinical results, and medication mistakes related to the delegation of medication administration. Keywords: Delegation obstacles, Community nursing, Delegation facilitators, Healthcare aide, Nurse delegation, Nursing aide, Registered nurse